Literacy as Involvement : the Acts of Writers, Readers, and Texts. - Brandt, Deborah (Southern Illinois University Press, 2011)
In Literacy as Involvement, Deborah Brandt examines the cultural and social roots of the acts of reading and writing. The book asks, for example, whether literacy is a natural growth of or a radical shift from orality. It questions the contrary views that literacy is either the learning of the conventions of language or is better understood as heightened social ability. Finally, it raises the possibility that knowing how to read and write is actually understanding how we respond during the acts of reading and writing. This examination of lite.